Localities Facing the Construction of Fossil-Fuel Power Plants. Two Experiences to Address the Hostile Face Electricity Infrastructures - Santander-Gana, M; Baigorrotegui-Baigorrotegui, G (Springer Nature, 2018)
This chapter is inspired by interesting experiences concerning electricity infrastructures facing local uprisings in two towns separated by a great distance: to address the hostile face building fossil-fuel power plants in mobilized citizen localities. Hostility levels are presented as different pulses, in which unexpected public demonstrations invade the public arena, possibly resulting from socio-technical closures in environmental impact evaluations. They mirror secret energy alliances, showing the influences and pressures of these transnational businesses. We also consider collective actions, incorporating interpretations and new and unexpected alliances. Our proposal draws on two qualitative, ethnographic studies about local socio-environmental conflicts contrary to the construction of fossil-fuel power plants, one of which arose in the Basque region of Spain, and the other in Coquimbo, Chile. Finally, we maintain that these geographically disperse studies, with their differing results, contribute to the discussion of locality as a framework of resistance against violent infrastructures, which goes beyond normalized processes and unfolds on other levels of action. © 2018, Springer International Publishing AG.